The Real Consequences of Financial Market Integration when Countries Are Heterogeneous - Kerstin Gerling (Oesterreichische Nationalbank (OeNB), 2008)
This paper studies the mechanisms through which financial integration affects the pattern of international capital flows and the domestic economic performances when explicitly accounting for wealth inequality on imperfect capital markets. Balancing the impact of a firm size and a credit rationing effect on the net credit position and on aggregate production will help predicting the distribution of gains and losses among and within countries on the basis of a country's aggregate wealth and its distribution. Altogether, the results contribute new explanations for some empirical puzzles. They also bear important implications for policy making, supranational treaty design and financial stability.
Keywords: D24; D31; D61; E44; F36; 330; international financial integration; inequality; imperfect capital markets and allocative efficiency